Modeling and Characterizing of an Enhanced Practical Terahertz Photoconductive Antenna - Fakieh, Aiman; Rmili, Hatem; Sobahi, Nebras (Communications in Mathematics and Applications, 2022)
Optical generation can be divided into photoconductive generation and optical rectification. Moreover, the generation of photoconductive is more efficient than optical rectification when standard laser oscillator systems are used. At photoconductive antenna (PCA), the efficiency and terahertz (THz) power generated are affected by different parameters (e.g. incident power of laser pump, dielectric properties and the applied DC bias voltage difference). In this research, four proposed designs of PCAs are presented and compared. Furthermore, microfabrication aspects and concerns have been considered in this study, which are rarely presented in the literature. Therefore, effects of different parameters are shown in this work such as adding adhesion layer in between electrodes and the substrate, varying of gap properties and dipole length. Output frequency, photocurrent and the total effective energy of different antenna models at different values of laser power have been studied and compared.
Keywords: Photoconductive antenna; Photocurrent; THz radiation; Laser pulse